A study on nose to brain drug delivery system: Advancements in Nasal Drug Delivery Systems for Therapeutic Goals (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Since ancient times, the nasal route has been used as a method for precisely dosing andadministering drugs for therapeutic and restorative purposes. This practise dates back to ancient times.Since the start of the 20th century, the fundamental effects of medications that are administered via thenasal route have been the focus of a growing amount of research and significance. Alternatives to theintra-nasal organisation of drugs include the parenteral route, which can be poorly constructed, and theoral route, which can lead to inadequately low bioavailability of medicines. Both of these routes arealternatives to the intra-nasal organisation of drugs. When it comes to delivering the considerablebeneficial effects of medicines, the intra-nasal organisation of drugs offers a potential alternative to theparenteral route that is traditionally used. In light of the aforementioned circumstances, it is of theutmost importance to acquire knowledge regarding the advantages and disadvantages of the differentnasal drug administration systems. As a result, the purpose of this research is to investigate thenumerous pharmacological dose forms that may be utilised in the field or by a fundamentalpharmaceutical organisation. The goal of this study is straightforward to improve our understanding of,and ability to put into practise, intra-nasal operations for the purpose of reaching certain therapeuticgoals.